Uma Abordagem baseada em rede de fornecimento de software para análise da evolução de ecossistemas de software - Pinheiro, Francisco Victor da Silva (2023)
Software Ecosystems (ECOS) are a set of actors and components that work as a unit, relating based on a common interest to provide solutions or services for the software industry. Software Supply Network (SSN), the diagram of software supply networks is a series of linked software, hardware, and service organizations that cooperate to meet market demands. For a better visualization and understanding of an ECOS, recent studies propose the modeling of the network formed, however, there is still no formalized modeling pattern for this area. The evolution of an ECOS happens when the ecosystem grows significantly in relation to itself and its actors and their respective relationships, which can be internal and external, as well as the expansion of relationships between the ECOS itself and other ECOS. Works focusing on evolution are scarce in the literature, bringing a range of research opportunities and challenges, such as: following the evolution of ECOS according to changes in the central platform, the evolution of the panorama of the internal and external user community. All this impacts the structure and life cycle of ECOS. To understand the state of the art of the literature, a systematic mapping of the literature was carried out on the terms: evolution, simulation, SSN modeling, models, health and quality of ECOS. In this context, this work proposes an approach to study, analyze, characterize and visualize the evolution of an ECOS through SSN modeling using the modeling tool and repository for ECOS Modeling models as support, in order to provide a broad view of the evolution of an ECOS under the bias of statistical data from SSN models enabling a quantitative, qualitative and percentage understanding of the evolution. The proposed approach was evaluated by undergraduate and graduate students, professors, researchers and software industry professionals through a Technology Acceptance Model (TAM) assessment in order to validate the proposal. Additionally, a case study was carried out using the proposed approach applied to ECOS SOLAR AND SIPPA. An interview was conducted with an industry professional linked to ECOS SIPPA to validate both the model presented and also to evaluate the evolution of ECOS SIPPA analyzed through the approach proposed in this work. Given the results obtained, the proposal proved to be suitable for the process of analyzing the evolution of ECOS.